(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The Present study was conducted in selected wards in Mymensingh municipality during the period of March- October, 2009 to know the existing condition of waste separation and its management ensuring better waste management practices. The study was performed with 100 respondents from 4, 6, 8 no. of wards in the Mymensingh municipality. Data related to characteristics of respondents as well as waste separation were collected using a questionnaire after testing and finalizing .The respondents involved in the study were maximum in middle aged (21-50 year) having the educational qualification in HSC level. The study also revealed that maximum respondents were with TK 10001-20000 as annual income having the family size within 5- 7 members. Maximum respondents in the study area were also involving the profession as business. The waste generation was higher with the increasing with the family members. In the study area waste separation approaches showed that among the separated waste, vegetable & fruit waste measured in the highest in case of solid kitchen waste having percentage as 64.80% compared to other types of wastes. The knowledge of waste separation was studied where it was observed that 20% respondent was well known with the facilities of waste separation. Most of The respondents also opinioned that they kept waste in containers and daily collection of waste preferably onto personal organization may be ensured better waste management. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22100 J. Environ. Sci. & Natural Resources, 6(2): 79-82 2013